John Dryden : a critical biography - Young, Kenneth; Bloom, Harold (Oxford : Oxford Clarendon Press, 1970)
A collection of twelve critical essays on the work of Dryden, arranged in chronological order of original publication.
Includes index.
Bibliography: p. 223-226.
Keywords: Dryden, John, -- 1631-1700 -- Criticism and interpretation; Dryden, John, -- 1631-1700 -- Criticism and interpretation; English literature -- History and criticism